Serum HDL and their subfractions are impaired in multisystem inflammatory syndrome in children (MIS-C) - Antonietta Giannattasio; Alice Castaldo; Michela Grieco; Monica Gelzo; Gustavo Cernera; Giuseppe Castaldo; Vincenzo Tipo (Journal of Translational Medicine)
Abstract Background Multisystem inflammatory syndrome in children (MIS-C) is a severe post-COVID condition due to a delayed hyperimmune response to SARS-CoV-2. High-density lipoproteins (HDL) are pivotal players in inflammatory and immune modulation through the remodeling of their subfractions. Methods This study aimed to evaluate serum levels of cholesterol, HDL, and HDL subfractions (HDL-SUB) to define their role in the pathogenesis of MIS-C and their potential use as biomarkers of this condition. We analyzed serum cholesterol, HDL and HDL-SUB (by capillary electrophoresis) in relation to serum values of biomarkers of inflammation and endothelial damage (by microfluidic immunoassays) in 48 patients with MIS-C at hospital admission and in 48 age- and sex-matched healthy controls. Results Serum cholesterol, as well as HDL, were significantly lower in MIS-C patients than controls. Serum cholesterol was inversely correlated with all biomarkers of inflammation, confirming the impact of cytokines on reverse cholesterol transport, whereas HDL values were inversely correlated with serum biomarkers of endothelial damage, suggesting a role of HDL in endothelial damage in MIS-C patients. Furthermore, we found a remodeling of HDL-SUB with a more pronounced decrease in small HDL that have anti-inflammatory activity. Conclusions These data confirm the severe impairment of reverse cholesterol transport in MIS-C and indicate serum HDL and HDL-SUB as potential useful diagnostic biomarkers of MIS-C.